Evaluation of Childhood Immunization Coverage in Jasikan District - Ntumy, R. (University of Ghana, 1995)
This is a study of the evaluation of the Expanded Programme on Immunization Coverage in the Jasikan District of the Volta Region of Ghana between October and December, 1995 with particular attention to childhood immunization coverage. This was a cross-sectional study using the WHO 30-7 cluster sampling method. The sample population were 219 children aged 12-23 months and their mothers. The primary objective of the study was to assess the childhood immunization coverage in the Jasikan District. In the study population 48.4 per cent of the children were fully immunized, 49.3 per cent partially and 2.3 per cent non immunized. The individual valid vaccine coverage was 83.1 per cent for BCG, 75 per cent for DPT3, 75.8 per cent for OPV3 and 67.1 per cent for measles. The drop out rate for DPT1-DPT3 was 8.2 per cent whilst that of BCG-measles was 18.3 per c e n t. Of the 182 children who had BCG recorded on their Road to Health cards, 4.4 per cent did not have the BCG scars. The completion of immunization schedules by one year among the 219 children was positively associated (P<0.005) with mothers’ parity being less than five children and mothers’ ability to mention at least two of the vaccine-preventable diseases. Formal education and place of delivery however, did not show any association with the completion of childhood immunization by one year. The recommendations given include: to issue Road to Health card to all children at birth in both government and private health facilities. ensure that BCG is administered to the newly born before discharging them from health facilities. intensification of home visits to trace defaulters so as to reduce drop-out rates, intensification of EPI health education at all places of contact and not necessarily only at child welfare clinics.
Theses (MPM)-University of Ghana